2002
DOI: 10.1021/bi016099j
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of an Insect Lysozyme Exhibiting Catalytic Efficiency at Low Temperatures,

Abstract: Bombyx mori lysozyme (BmLZ), from the silkworm, is an insect lysozyme. BmLZ has considerable activity at low temperatures and low activation energies compared with those of hen egg white lysozyme (HEWLZ), according to measurements of the temperature dependencies of relative activity (lytic and glycol chitin) and the estimation of activation energies using the Arrhenius equation. Being so active at low temperatures and low activation energies is characteristic of psychrophilic (cold-adapted) enzymes. The three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 38 publications
1
28
2
Order By: Relevance
“…Most cold-adapted enzymes come from psychrophilic bacteria and are characterized by a high specific enzymatic activity in the range of 0-30°C (Gerday et al 2000). In this work we found that the optimal temperature for Ms-lyz was 15°C lower than that of hen egg white lysozyme, as previously reported for the coldadapted silkworm lysozyme (Matsuura et al 2002). Also, the specific activity of Ms-lyz was about twice that of hen egg white lysozyme at 5°C as reported for cold adapted enzymes ( Figure 3).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Most cold-adapted enzymes come from psychrophilic bacteria and are characterized by a high specific enzymatic activity in the range of 0-30°C (Gerday et al 2000). In this work we found that the optimal temperature for Ms-lyz was 15°C lower than that of hen egg white lysozyme, as previously reported for the coldadapted silkworm lysozyme (Matsuura et al 2002). Also, the specific activity of Ms-lyz was about twice that of hen egg white lysozyme at 5°C as reported for cold adapted enzymes ( Figure 3).…”
Section: Resultssupporting
confidence: 84%
“…Hen egg white lysozyme has been expressed in eukaryotic systems such as Aspergillus (Archer et al 1990), and yeast (Nakamura et al 1993), and the insect lysozyme from Bombyx mori was expressed in Picha pastoris (Matsuura et al 2002). However, bacterial expression of lysozyme is not trivial due to the problems with protein refolding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to mutational studies, the involvement of these factors in protein adaptation is suggested from comparative studies between psychrophilic enzymes and their heat-stable homologues based on homology models and 3D structures. An increased number of crystallographic structures of psychrophilic enzymes from bacteria and cold-adapted fishes have been previously elucidated (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) (29) and fish trypsin (37). Other structures should become available soon, as crystals of three other cold-active enzymes have been obtained (43)(44)(45).…”
Section: Psychrophilic Enzymesmentioning
confidence: 99%
“…Together with a variety of potent antibacterial and antifungal peptides, insect lysozyme is induced and secreted into the blood (hemolymph), which becomes a hostile environment for bacterial growth (Hultmark 1996). Insect lysozyme is generally considered as a basic, heat-stable, and cationic protein, and has been studied for structural and functional stability for the past decades (Matsuura et al 2002).…”
Section: Introductionmentioning
confidence: 99%